Analysis of Efficiency and Effectiveness Level Collection of Total Retribution of Waropen Regency - Pieter N de Fretes (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the average growth rate in the value of total regional levies in Waropen Regency, the efficiency level of collecting total regional retributions in Waropen Regency, the effectiveness of collecting total regional levies in Waropen Regency during the period 2014 - 2020 and projected total receipts of Regency Regional Levies. Waropen in the future. The analytical tools used in this study include; Relative growth ratio, efficiency level, effectiveness and projection level. The data used are primary and secondary data. Based on the results of the analysis, it is known that the realization of the total revenue of regional levies shows a positive growth ratio, with an average growth of 13.31% per year. Overall, the regional financial performance with respect to the total collection value of Regional Levies in Waropen district is included in the Efficient category, with an average efficiency level of 62.08% per year. The results of the measurement of the effectiveness level show that when compared to the total potential of regional levies in Waropen district, on average the percentage of realization of total regional levies during the observation period is only 63.22%. Referring to the financial performance criteria, the average percentage of 61.11% indicates that the level of management of total regional levies in Waropen district is in the